Enigmatic variation - Roberts, I; Vyas, P (American Society of Hematology, 2011)
Variability in presentation and prognosis of transient myeloproliferative disorder (TMD) in infants with Down syndrome (DS) has perplexed clinicians and scientists for decades and is explored in this issue of Blood by Gamis and colleagues from the Children's Oncology Group (COG).